Characterization of the nests of the leaf-cutting ant Atta cephalotes (Hymenoptera: Myrmicinae) in Cali (Colombia) - MONTOYA-LERMA, JAMES; CHACÓN DE ULLOA, PATRICIA; ROSARIO MANZANO, MARIA DEL (Revista Colombiana de Entomología, 2006)
The proportion of green zones with the presence of nests and the level of infestation of the leaf-cutting ant, Atta cephalotes, were determined in three urban areas of Cali. Between March and April 2002, a total of 143 green zones was evaluated, consisting of parks, traffic islands, verges and other open spaces occupying a total of 1.276.131 m2. The highest proportion (89%) of the green areas had low/medium infestations, i.e. less than half of the area was occupied by ant nests. The remainder (11%) showed high infestations, with more than half of the area colonized by leaf-cutting ants. Most (68%) of the nests were found on naturally level terrain, followed by steep terrain such as verges (27%) and some nests located near human dwellings. Area of the nests ranged from 1-211 m2. A direct correlation was found between the number of quadrants needed to enclose 50% of the nest entrances and the total nest area (r= 0, 70). Based on this methodology, it is possible to carry out a rapid and reliable estimate of the degree of infestation of areas affected by leaf-cutting ants as a preventive measure for their control or management.